Relative Pricing and Efficient Allocation in Blockchains - Abdoulaye Ndiaye (CESifo GmbH, 2024)
This paper investigates how relative pricing schemes can achieve efficient allocations in blockchain systems featuring multiple transaction queues under a global capacity constraint. I model a capacity-constrained blockchain where users submit transactions to different queues—each representing a submarket with unique demand characteristics—and decide to participate based on posted prices and expected delays. I find that revenue maximization tends to allocate capacity to the highest-paying queue, whereas welfare maximization generally serves all queues. Optimal relative pricing of different queues depends on factors such as market size, demand elasticity, and the balance between local and global congestion. My results have implications for the implementation of local pricing for evolving blockchain architectures, including parallel transaction execution, directed acyclic graph (DAG)-based systems, and multiple concurrent proposers.
Keywords: 330; blockchain; fintech; transactions; parallel execution; fee markets; consensus